Effects of melatonin on carbon tetrachloride-induced changes in rat serum - Ogeturk, M; Kus, I; Kavakli, A; Zararsiz, I; Ilhan, N; Sarsilmaz, M (Springer, 2004)
Carbon tetrachloride (CCl4) is a volatile organic chemical, which causes tissue damage, especially to the liver and kidney. In experimental animals it has been shown to be carcinogenic. This study was designed to evaluate the effects of exogenous melatonin administration on the CCl4-induced changes of some biochemical parameters in rat blood. Twenty-four male Wistar rats were randomly divided into three equal groups: Control, CCl4 and CCl4 Plus melatonin (CCl4+MEL). Rats in CCl4 group were injected subcutaneously with CCl4 0.5 ml/kg in olive oil while rats in CCl4+MEL group were injected with CCl4 (0.5 ml/kg) plus melatonin (25 mg/kg in 10% ethanol) every other day for one month. Control rats were treated with olive oil. Serum urea, creatinine, total protein, albumin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), total and conjugated bilirubin, alkaline phosphatase (ALP), gamma-glutamyl transferase (gamma-GT), total iron, and magnesium levels were determined. Serum AST, ALT, total and conjugated bilirubin, ALP,gamma-GT, and total iron levels were significantly higher in CCl4-treated rats than in the controls, while urea, total protein, and albumin levels were significantly lower. Melatonin treatment did not cause a significantly change in serum urea, total protein, and albumin levels. However, the elevations in AST, ALT, total and conjugated bilirubin, ALP, gamma-GT, and total iron levels induced by CCl4 injections were significantly reduced by melatonin. On the other hand, melatonin administration significantly decreased serum magnesium levels. These results indicate that melatonin could be a protective agent against the CCl4 toxicity in rats, most likely through its antioxidant and free radical scavenger effects.
Keywords: carbon tetrachloride; melatonin; toxicity; blood biochemistry